2021
DOI: 10.15560/17.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the vascular plants of Alert (Ellesmere Island, Canada), a polar desert at the northern tip of the Americas

Abstract: Long-term monitoring is critical to guide conservation strategies and assess the impacts of climatic changes and anthropogenic activities. In High Arctic ecosystems, information on distribution and population trends of plants is dramatically lacking. During two field expeditions in 2018 and 2019, we conducted a systematic floristic survey together with opportunistic collecting in the polar desert surrounding Alert (Nunavut, Canada) to update past vascular plant inventories. We recorded 58 species, of which 54 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…A total of 264 vegetation plots were sampled. Of the 77 vascular plant species ever recorded in the study area (Desjardins et al 2021a), 58 were found during this study, as well as five cryptogams (biological soil crust, blue-green algae, lichen, macrofungus, and moss). Among the 58 vascular species, 54 were found within the vegetation plots while four rare species were found only through opportunistic sampling (i.e., collected along marked trails and while traveling within the study area, outside of vegetation plots), namely Carex aquatilis Wahlenberg var.…”
Section: Overview Of Floristic Compositionmentioning
confidence: 73%
See 4 more Smart Citations
“…A total of 264 vegetation plots were sampled. Of the 77 vascular plant species ever recorded in the study area (Desjardins et al 2021a), 58 were found during this study, as well as five cryptogams (biological soil crust, blue-green algae, lichen, macrofungus, and moss). Among the 58 vascular species, 54 were found within the vegetation plots while four rare species were found only through opportunistic sampling (i.e., collected along marked trails and while traveling within the study area, outside of vegetation plots), namely Carex aquatilis Wahlenberg var.…”
Section: Overview Of Floristic Compositionmentioning
confidence: 73%
“…Canonical Correspondence Analysis (CCA) was used to identify primary relationships between cover data and environmental variables (Legendre and Legendre 2012). Environmental variables included: (1) Normalized difference vegetation index (NDVI) computed from the pan-sharpened multispectral satellite picture of the study area, (2) elevation from the Canadian Digital Elevation Model (DEM) (Natural Resources Canada 2015), ( 3) slope derived from the DEM using ArcGIS, (4) distance to the nearest perennial snowbank derived from the habitat map (Desjardins et al 2021a), ( 5) location with respect to a perennial snowbank (binary state with 1 indicating location below a snowbank and 0 location above or beside a snowbank); this binary variable was added since the distance to the nearest perennial snowbank may not fully capture the effect of snowbanks, considering that sites spatially close to a snowbank but located upslope or besides the snow patch do not actually benefit from melt water that flows downslope, (6) distance to the nearest lake or pond derived from the habitat map and from the Topographic Data of Canada -CanVec Series (Natural Resources Canada 2017), ( 7) distance to the nearest river derived from Topographic Data of Canada -CanVec Series (Natural Resources Canada 2017), and (8) distance to the nearest ocean shore derived from Topographic Data of Canada -CanVec Series (Natural Resources Canada 2017). These eight environmental variables were not collinear, as shown by the variance inflation factor (VIF; regclass package in R software, R Core Team 2020) being <10.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations